2009
DOI: 10.1097/gco.0b013e328321e44b
|View full text |Cite
|
Sign up to set email alerts
|

Urogynaecological problems in pregnancy and postpartum sequelae

Abstract: There is radiological evidence supporting pelvic floor injury following vaginal childbirth and epidemiological evidence for the relationship between vaginal delivery and urinary incontinence and pelvic organ prolapse. Rigorous long-term studies are needed to identify the direct relationship between these two phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Panayi and Khullar reported that approximately 20% of multiparous women with SUI during the first trimester had levator ani muscle defects on magnetic resonance imaging compared to nulliparous women [19]. Previous pelvic floor trauma after vaginal delivery resulting in poor support for the urethra may explain why multiparous women have a higher prevalence of SUI [20].…”
Section: Discussionmentioning
confidence: 99%
“…Panayi and Khullar reported that approximately 20% of multiparous women with SUI during the first trimester had levator ani muscle defects on magnetic resonance imaging compared to nulliparous women [19]. Previous pelvic floor trauma after vaginal delivery resulting in poor support for the urethra may explain why multiparous women have a higher prevalence of SUI [20].…”
Section: Discussionmentioning
confidence: 99%
“…These injuries may persist following vaginal delivery and cause the development of urinary incontinence and POP [16,17]. In addition to the evaluation of parity and menopausal status-which have previously been reported as potential risk factors for POP [3,18,19]-other factors, such as age at first delivery, time interval from delivery to work, and position during delivery, were also analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is debatable whether pregnancy alone would be enough reason to cause impairments that could cause urinary incontinence. However, it is known that many women present this symptom during pregnancy and fail to report it after delivery (7,19) . It may be that these women present a greater risk of developing urinary incontinence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy and delivery are the main risk factors associated with SUI, especially during the reproductive years (4)(5)(6)(7) , particularly vaginal delivery (8) , due to the damage that it can cause to integrity of muscles and nerves of the pelvic floor. These muscles and nerves represent an important factor in maintenance of urinary continence.…”
Section: Descritores: Incontinência Urinária; Parto Normal; Cesárea; mentioning
confidence: 99%